New fossils, systematics, and biogeography of the oldest known crown primate Teilhardina from the earliest Eocene of Asia, Europe, and North America. Issue 128 (March 2019) - Morse, Paul E.; Chester, Stephen G.B.; Boyer, Doug M.; Smith, Thierry; Smith, Richard; Gigase, Paul; Bloch, Jonathan I.
Abstract: Omomyiform primates are among the most basal fossil haplorhines, with the oldest classified in the genus Teilhardina and known contemporaneously from Asia, Europe, and North America during the Paleocene–Eocene Thermal Maximum (PETM) ∼56 mya. Characterization of morphology in this genus has been limited by small sample sizes and fragmentary fossils. A new dental sample ( n  = 163) of the North American species Teilhardina brandti from PETM strata of the Bighorn Basin, Wyoming, documents previously unknown morphology and variation, prompting the need for a systematic revision of the genus. The P4 of T. brandti expresses a range of variation that encompasses that of the recently named, slightly younger North American species ' Teilhardina gingerichi, ' which is here synonymized with T. brandti . A new partial dentary preserving the alveoli for P1-2 demonstrates that T. brandti variably expresses an unreduced, centrally-located P1, and in this regard is similar to that of T. asiatica from China. This observation, coupled with further documentation of variability in P1 alveolar size, position, and presence in the European type species T. belgica, indicates that the original diagnosis of T. asiatica is insufficient at distinguishing this species from either T. belgica or T. brandti . Likewise, the basal omomyiform ' Archicebus achilles ' requires revision to be distinguished from Teilhardina . Results from a phylogenetic analysis of 1890 characters scored for omomyiforms, adapiforms, and other euarchontan mammals produces a novel clade including T. magnoliana, T. brandti, T. asiatica, and T. belgica to the exclusion of two species previously referred to Teilhardina, which are here classified in a new genus ( Bownomomys americanus and Bownomomys crassidens ). While hypotheses of relationships and inferred biogeographic patterns among species of Teilhardina could change with the discovery of more complete fossils, the results of these analyses indicate a similar probability that the genus originated in either Asia or North America.